Special attention is given to the project of the Informational System "Planned for Science in the NAPN of Ukraine" - Zadorozhna, N.T.; Petrushko, V.A.; Tukalo, S.M. (Інститут програмних систем НАН України, 2015)
The paper presents an information system «Planning research at NAPS Ukraine», developed to support the automation documentary process оf planning research. The system is designed as a corporate intranet portal based on Microsoft Office SharePoint Server 2007 with application tools and templates designed according the requirements analysis of subject area. There are goals and objectives of the system, the subject area, document types and requirements. Project decision system described as the information model (47 documents and 253 common fields), steps to project back end and front end system, menu, pages and features of the portal.